Role of ROS and Nutritional Antioxidants in Human Diseases - Liu, Zewen; Ren, Zhangpin; Zhang, Jun; Chuang, Chia-Chen; Kandaswamy, Eswar; Zhou, Tingyang; Zuo, Li (Frontiers in Physiology, 2018)
Overproduction of reactive oxygen species¬ (ROS) have been implicated in the development of various chronic and degenerative diseases such as cancer, respiratory, neurodegenerative and digestive diseases. Under physiological conditions, the concentrations of ROS are subtlety regulated by antioxidants, which can be either generated endogenously or externally supplemented. A combination of antioxidant-deficiency and malnutrition may render individuals more vulnerable to oxidative stress, which increases the risk of cancer occurrence. In addition, antioxidant defense can be overwhelmed during sustained inflammation such as in chronic obstructive pulmonary diseases, inflammatory bowel disease, and neurodegenerative disorders. Certain antioxidant vitamins, such as vitamin D, are essential in regulating biochemical pathways that lead to the proper functioning of the organs. Antioxidant supplementation has been shown to attenuate endogenous antioxidant depletion thus alleviating associated oxidative damage in some clinical research. However, some results have shown that antioxidants exert no favorable effects on disease progression. Thus, more studies are warranted to investigate the complicated interactions between ROS and different types of antioxidants for restoration of the redox balance under pathologic conditions. This review highlights the potential roles of ROS and nutritional antioxidants in the pathogenesis of several redox imbalance-related diseases and the attenuation of oxidative stress-induced damages.